2010
DOI: 10.1186/1471-213x-10-95
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline-controlled transgene activation using the ROSA26-iM2-GFP knock-in mouse strain permits GFP monitoring of DOX-regulated transgene-expression

Abstract: BackgroundConditional gene activation is an efficient strategy for studying gene function in genetically modified animals. Among the presently available gene switches, the tetracycline-regulated system has attracted considerable interest because of its unique potential for reversible and adjustable gene regulation.ResultsTo investigate whether the ubiquitously expressed Gt(ROSA)26Sor locus enables uniform DOX-controlled gene expression, we inserted the improved tetracycline-regulated transcription activator iM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In line with our results showing disparate enrichment between organs, various reports have emphasized that various TG mouse models equipped, genetically manipulated in different genes expressed variable amounts of mRNA in peripheral tissues [40]. More specifically, the pCAG promoter in the Rosa26 locus suffers from mosaic transgene expression among organs [41] and the responder gene expression was moderate and highly variable between and within different tissues [42]. …”
Section: Resultssupporting
confidence: 87%
“…In line with our results showing disparate enrichment between organs, various reports have emphasized that various TG mouse models equipped, genetically manipulated in different genes expressed variable amounts of mRNA in peripheral tissues [40]. More specifically, the pCAG promoter in the Rosa26 locus suffers from mosaic transgene expression among organs [41] and the responder gene expression was moderate and highly variable between and within different tissues [42]. …”
Section: Resultssupporting
confidence: 87%
“…To completely restrict AE expression to haematopoietic cells, we transplanted whole bone marrow (BM) from compound ROSA26-iM2-tetO-GFP/TgPtet-AML1-ETO (R26/AE) mice into lethally irradiated recipients (Rhoades et al, 2000 ; Wortge et al, 2010 ). As illustrated in Fig 1 A, in reconstituted mice the expression of AE and the GFP co-reporter gene can be regulated by administering doxycycline (DOX) [for review see (Bockamp et al, 2002 ; Bockamp et al, 2008 )].…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Fig 1 A, in reconstituted mice the expression of AE and the GFP co-reporter gene can be regulated by administering doxycycline (DOX) [for review see (Bockamp et al, 2002 ; Bockamp et al, 2008 )]. We have previously shown that the R26-iM2 effector mouse strain directed mosaic transgene expression to lineage − /c-Kit + /Sca1 + (L − K + S + ) haematopoietic progenitor cells and to different adult blood lineages (Wortge et al, 2010 ). In line with this mosaic expression pattern, we found conditional GFP activation in a percentage of long-term repopulating haematopoietic stem cells (LT-HSC, L − K + S + CD150 + CD48 − Flt3 − CD34 − ), short-term repopulating haematopoietic stem cells (ST-HSC, L − K + S + CD150 + CD48 − Flt3 − CD34 + ), common myeloid progenitors (CMPs, L − K + S − IL7Rα − CD34 + FcγRII/III low ), granulocyte macrophage progenitors (GMPs, L − K + S − IL7Rα − CD34 + FcγRII/III + ), megakaryocyte erythrocyte progenitors (MEPs, L − K + S − IL7Rα − CD34 − FcγRII/III low ) and common lymphoid progenitors (CLPs, LK int S int IL7Rα + ) of R26/AE reconstituted recipients ( Fig 1 B, Supporting Information Fig S1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this locus has been described to be ubiquitously active ( 32 ), expression of transgene cassettes with different transcription control elements underlies non-predictable expression characteristics ( 52 , 53 ). While Tet promoter driven transgene expression could be achieved to a certain degree, mosaic and also loss of expression have been reported ( 34 , 54 56 ). This suggests that the Tet promoter is affected by epigenetic silencing, although the underlying mechanism remained elusive.…”
Section: Discussionmentioning
confidence: 99%